El Rol y la Importancia del Centro Regulador Médico como eje neurálgico en la organización y gestión de los Servicios Prehospitalarios de Emergencias Médicas (SEM) - Llerena-Cárdenas, Simeón David (2026)
Background: The effectiveness of Emergency Medical Services (EMS) depends on robust systemic coordination, where the Medical Regulatory Center (MRC) acts as the central governing body. Objective: To analyze the MRC's role as the “neural axis” of EMS, examining its functions, its impact on quality and patient safety, and the challenges it faces.Findings: The MRC functions as the architectural axis that unifies dispatch, first response, and transport. Its key functionsinclude the standardization of protocols, enabling the creation of efficient, regionalized systems of care. Its impact on quality is direct, mandating adherence to evidence-based practices and using data analysis for continuous quality improvement (CQI), transforming EMS into a high-reliability organization. However, the MRC faces significant challenges, such as assigning legal liability in a multi-agency environment, managing ethical dilemmas in triage, andovercoming regulatory barriers. Conclusion: The MRC is an indispensable entity for a modern EMS, acting as the engineof standardization, integration, and quality. Strengthening its authority is fundamental to ensuring the resilience and effectiveness of emergency response.